Características anatômicas da folha de Erythroxylum tortuosum Mart. (Erythroxylaceae) em ambiente de cerrado stricto sensu e campo rupestre - Dias , Mariana Virginia de Freitas (2019)
Many species of this plant formation have evolved under strong selective pressure by herbivores, they are well adapted to dystrophic, acidic, aluminum rich soils, and resist periods of drought, often prolonged. It is important to emphasize the relevance of Cerrados as a unique genetic resource highlighting the need to protect and preserve its genetic diversity. Although many of the structural adaptations of cerrado plants are known, the information is limited to a very small number of species. The aspects o f the morphology and anatomy of the majority of the representatives of the cerrado are unknown to the richness and diversity of this formation. Based on this information, this work aimed at a descriptive and quantitative morphological study of Erythroxylum tortuosum Mart. leaf. (Erythroxylaceae) present in two environments: cerrado stricto senso and rupestre field. For the accomplishment of the studies, 24 fully developed leaves of individuals present in two environments were collected and fixed. For the quantitative anatomy study the following analyzes were obtained: area, length, width and mass of the leaves, stomatal density, polar and equatorial diameters of the stomata, thickness of leaf, mesophyll, epidermis and cuticles of the adaxial and abaxial face s and the palaquadic parenchyma and spongy parenchyma. As for its anatomy, it was observed glabrous and uniseriate epidermis when seen in cross-section. The stomata are paracitic type and occur in the abaxial face, classifying the species as hypoestomatic. The mesophyll is dorsiventral type, with dense vascular system a nd the vascular bundle is collateral type. The venation is pinnate type, camptodroma, brochidodroma, with a network of dense veins and pseudo secondary veins. Statistical differences were found for almost all analyzed variables, suggesting that different environmental conditions may influence the development of the plant.